2019
DOI: 10.1002/ps.5673
|View full text |Cite
|
Sign up to set email alerts
|

Antifeedant, contact toxicity and oviposition deterrent effects of phyllostine acetate and phyllostine isolated from the endophytic fungus Diaporthe miriciae against Plutella xylostella larvae

Abstract: BACKGROUND Larvae of the diamond back moth (DBM), Plutella xylostella, are destructive cabbage pests causing economic losses worldwide. Continuous application of synthetic pesticides to control this pest has resulted in environmental pollution and resistant pest strains. Thus, there is a crucial need to seek natural alternatives with minimal detrimental effects. This study was designed to investigate the antifeedant activities of endophytic fungi of Cyperus iria and to determine the antifeedant, contact toxici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Previous studies have confirmed that some species of the Aspergillus genus contribute to the death of members of the insect orders Hymenoptera [ 74 ], Lepidoptera [ 75 ], Coleoptera [ 76 ] and Diptera [ 77 ]. Furthermore, some species of the Diaporthe genus are pathogens of dipteran [ 78 ] and lepidopteran species [ 20 , 79 ] and can result in the death of insects [ 61 ]. However, there is no firm evidence indicating that Botryosphaeria sp., Aspergillus sp.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have confirmed that some species of the Aspergillus genus contribute to the death of members of the insect orders Hymenoptera [ 74 ], Lepidoptera [ 75 ], Coleoptera [ 76 ] and Diptera [ 77 ]. Furthermore, some species of the Diaporthe genus are pathogens of dipteran [ 78 ] and lepidopteran species [ 20 , 79 ] and can result in the death of insects [ 61 ]. However, there is no firm evidence indicating that Botryosphaeria sp., Aspergillus sp.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, 106 compounds derived from Diaporthe exhibiting biological activities, such as cytotoxic, antifungal, antibacterial, antiviral, antioxidant, anti-inflammatory, phytotoxic, antiparasitic, and herbicidic activities, have been studied (Ash et al, 2010;Meepagala et al, 2018;Xu et al, 2021). Two cyclohexeneoxidediones, phyllostine acetate (1) and phyllostine (2), from the fungus Diaporthe miriciae, showed insecticidal activity against Plutella xylostella larvae (Ratnaweera et al, 2020). Meepagala et al (2018) isolated a compound from the liquid medium extract of Diaporthe eres, identified as 3,4-dihydro-8-hydroxy-3,5-dimethylisocoumarin (1), which has larvicidal activity against Ae.…”
Section: Discussionmentioning
confidence: 99%
“…200-202 °C. 1 Compounds I-11−I-46 were synthesized by means of the procedure described for I-10. The physical data for I-11-I-46 are provided in the Supporting Information.…”
Section: 5-dichloro-1-(1-trifluoromethylethenyl)benzenementioning
confidence: 99%